Multiple psychotherapeutic approaches and perspectives on eco-anxiety - Raile, Paolo (Frontiers in Psychology, 2023)
In highly diverse psychotherapy practice, psychotherapists with their individual schemas and personalities meet patients who are just as individual, each with their own partially dysfunctional schemas, personalities, and life-worlds. To still treat successfully, intuition formed through experience is often used and interventions or techniques appropriate to the specific situation and psychotherapist-patient-constellation are chosen. Therefore, having some range of possible perspectives and (treatment) actions is helpful. The psychotherapeutic field offers a variety of such perspectives, approaches, and techniques from which practitioners can choose depending on the situation, as exemplified by the various approaches and their specific treatment options for various patients with full spectrum of Eco-Anxiety manifestations.